POPULATION OF MAST CELLS AND GLOBULE LEUKOCYTES IN THE BRONCHOPULMONARY SYSTEM OF GOATS EXPERIMENTALLY-INFECTED WITH DICTYOCAULUS FILARIA - S. MAHMOUD, G.; J. ALWAN , M. (The Iraqi Journal of Veterinary Medicine, 1990)
The population of the mast cells (MCs) and globule leukocytes (GLS) in bronchi of goats infected with D.Filaria was studied as well as the histochemical changes occurring in goblet cells and mucosal glands in the airways of goats during postpatent of Dictyocaulus infection. It was shown that the population of these cells was associated with parasitic infection and they play a role in the immune response of host against parasitic infection. Histochemical studies showed that the mucosubstance of the airways of parasitic goats was a mixture of sulphomucin and sialomucin.